Optimasi kinerja reaktor pirolysis biomassa dengan penambahan pipa udara - Kemas Ridhuan; Fajar Khusaini; Ridwan Ridwan (TURBO [Tulisan Riset Berbasis Online], 2022)
The pyrolysis reactor is a tool that functions to decompose organic compounds from biomass materials which is carried out by a heating process without or little air with temperatures ranging from 300-600°C. The results obtained from the pyrolysis reactor process are charcoal and liquid smoke. The existing air will accelerate the process of biomass oxidation, but if there is excess air it will cause combustion of the biomass so that most of it will be oxidized and decomposed into smoke and this will cause less charcoal yield. However, without air, the pyrolysis process will take longer. Therefore, an ideal air requirement is needed so that the effectiveness of this biomass pyrolysis process can be maintained because it will produce optimal charcoal and liquid smoke. The purpose of this research is to find out how many air pipes for the pyrolysis reactor are needed in this combustion process and how long the time and temperature of the pyrolysis process combustion and how much charcoal and liquid smoke are obtained. This research was conducted at the Mechanical Engineering Laboratory of the University of Muhammadiyah Metro, this study used a pyrolysis reactor with a diameter of 40 cm, height 50 cm, air pipe diameter inch with variations in the number of 1,3 and 5. Using 8 kg of corncob biomass. Straight pipe condenser with 12 mm diameter copper material 3 m long, outer pipe diameter 4 inch. The results showed that the highest pyrolysis temperature in air pipe 5 was 485°C with a pyrolysis process time of 120 minutes and the lowest temperature in pipe 1 was 353°C with a pyrolysis process time of 185 minutes. The results of the most liquid smoke in air pipe 5 are 0.5 liters or 6.25% and the least liquid smoke results are in air pipes 1 as much as 0.32 liters or 4.0% For the highest charcoal yields in air pipes 1 weighing 4 kg or 50% and for charcoal yields at least on air pipe 5 of 3.2 kg or 42.5%. The highest pH level in the air pipe 1 is 3.43 and the lowest level in the air pipe is 3.11.